Trauma-Informed Care in the health-care for transgender and gender-diverse adults: a scoping review - Borcherding, Hannah; Itz, Marlena L.; Strauß, Bernhard; Nieder, Timo O. (Frontiers in Psychiatry, 2025)
Transgender and gender-diverse (TGD) individuals frequently experience discrimination, minority stress, microaggressions, and traumatic events, including physical and sexual violence. It is essential to consider these traumatic experiences in clinical practice, as negative experiences within the health-care system can deter TGD individuals from seeking necessary support. However, many health-care professionals lack adequate training to respond effectively to the needs of TGD individuals. Trauma-Informed Care (TIC) presents a potential solution by encouraging professionals to recognize trauma, prioritize safety and transparency, and adapt their behavior to minimize distress. This scoping review aims to provide an overview of the existing empirical literature for the application of TIC in TGD health-care settings. A comprehensive literature search was conducted using the EBSCO, PubMed, and Scopus databases to identify studies examining TIC specifically within TGD health-care contexts. The review followed the PRISMA checklist extension for scoping reviews. Inclusion criteria required that studies analyze original data on the implementation of TIC in TGD health-care settings. The included studies were analyzed to assess the TIC principles included and their impact on health outcomes. The review identified four studies that met the eligibility criteria. Findings suggest that while TIC can provide significant benefits in fostering safe and affirming health-care environments for TGD individuals, the literature remains mixed and scarce. Methodological diversity and varying definitions of TIC complicate the synthesis of results. Gaps in research and inconsistencies in its application were highlighted. The findings underscore the potential of integrating TIC principles into health-care for TGD populations, as current frameworks often overlook their unique needs. For future research it seems crucial to conduct effectiveness studies of TIC such as randomized-controlled trails, standardize TIC definitions, develop robust outcome measures and explore TIC in various contexts. This review highlights the potential of TIC in the healthcare for TGD individuals while emphasizing the need and providing directions for further research.